AI-Enhanced Cloud Data Systems for Healthcare (Global Journal of Computer Science and Technology, 2025)
AI data systems support Healthcare cloud computing through automated workflow operations Our AI system presents four innovative devices for medical and research data 1 a Data Cleaning Device 2 a Data Optimization Device 3 a Multi-Cloud Optimizer and 4 a Data Logger A detailed description includes their design process the healthcare application pipeline for electronic health record cleaning medical image storage multi-cloud deployment capabilities and secure audit functionality The device connections are illustrated through architectural diagrams Data quality rises while processing speed improves alongside cost reduction by adopting a Performance evaluation system compared to conventional information systems The primary focus of our approach centres around innovative methods of data quality enhancement and storage system development alongside compliance requirements
Keywords: AI; healthcare; data cleaning device; data optimization device; multi-cloud optimizer; data logger